The Role of Teacher Cooperation in Promoting Learner Autonomy: Perspectives from Focus-group Inservice Teacher Training - Eren, Ömer (My University, 2023)
Learner autonomy in language learning and teaching has been a notable focus of interest, and there is an abundance of literate available on this topic. However, how learner autonomy is practised in the language classroom has not received much attention. To address this gap, the current study set out to investigate English language instructors' classroom practices in public and private universities, and the potential contribution of inservice teacher training (INSET) in promoting learner autonomy through quantitative and qualitative analyses. Findings revealed that there is partial learner autonomy in institutions and the type of university (public or private) did not differ in terms of classroom practices and teaching strategies. Analyses of reflective writing papers also showed that inservice teacher training plays a significant role in promoting learner autonomy in language classes. Perceived impacts, drawbacks, and envisioning the future implementations of INSET programmes are discussed as emerging themes from thematic analyses.
Keywords: Language learning; learner autonomy; inservice teacher training; teacher collaboration